A longitudinal assessment of the antibody response to SARS-CoV-2 infection in the New Mexican population - Frances M. Twohig; Tonilynn M. Baranowski; Chunyan Ye; Michelle Harkins; Steven B. Bradfute (PLoS ONE, 2025)
While many studies have assessed immune responses to SARS-CoV-2 infection, none have studied functional antibody responses before and after vaccination of exposed patients in New Mexico in the United States. Here, we evaluate antibody binding, antibody neutralization, and antibody dependent cell-mediated cytotoxicity (ADCC) responses from convalescent patients between September 2020 and April 2021. Our results indicate that binding, neutralizing, and ADCC titers remained durable over an estimated 4-month period or were boosted by vaccination. Antibody binding titer stability was comparable to that of antibodies against four common viruses. Hispanic and Latino responses were similar to non-Hispanic/Latino responses in this cohort. Overall, these data shed light on functional antibody responses to SARS-CoV-2 in pre-alpha variant waves in New Mexico.